(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to test Kaldor’s hypothesis of the relationship between industrial production and economic growth in Sudan during the period from 2000-2022, considering that industrial production is the main engine of economic growth. It used autoregressive model, Co- integration, error correction model and Granger causality, and achieved the verification of Kaldor’s hypothesis in the Sudan economy, There is a balanced relationship between industrial production and economic growth, and a causal relationship in one direction from industrial production to economic growth, and it recommended the necessity of adopting industrial policies that support local production by increasing the number of investment portfolios and funds, which helps in mobilizing savings and directing them to investment in the industrial sector to expand the base of Production.